Hubungan Cash Holding dan Nilai Perusahaan di Indonesia - Sutrisno, Bambang (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This paper aims to examine the effect of cash holding on firm value in Indonesia. This study tested empirically for the existence of a linear relationship between cash holding and firm value. Then the study examines whether or not a quadratic relationship exists. A total of 115 manufacturing firms listed on the Indonesia Stock Exchange from 2010 to 2014 were examined. This study employs panel regression with fixed effect model. The results show that a linear relationship exists between cash holding and firm value. However, a quadratic relationship does not appear between cash holding and firm value of Indonesian manufacturing firms. Thus, the result of this study supports pecking order theory